2014
DOI: 10.1108/f-09-2012-0067
|View full text |Cite
|
Sign up to set email alerts
|

KPIs for facility's performance assessment, Part II: identification of variables and deriving expressions for core indicators

Abstract: Purpose-The purpose of this paper is to identify key variables that affect the quantifiable key performance indicators (KPIs) and to derive equations to measure these indicators. Qualitative KPIs are also discussed in terms of the aspects that need to be covered while carrying out qualitative performance assessment. Design/methodology/approach-A combination of literature and an industry opinion-based qualitative approach is applied to develop equations to calculate the quantifiable KPIs. A facility asset manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 38 publications
(91 reference statements)
0
34
0
Order By: Relevance
“…Within the first 50 documents, the following 20 articles have been taken into account: [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39]. All of these articles meet the requirements, since they indicate a number of KPIs that can be used to manage the infrastructure, and most of them also display different categorizations.…”
Section: Resultsmentioning
confidence: 99%
“…Within the first 50 documents, the following 20 articles have been taken into account: [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30], [31], [32], [33], [34], [35], [36], [37], [38], [39]. All of these articles meet the requirements, since they indicate a number of KPIs that can be used to manage the infrastructure, and most of them also display different categorizations.…”
Section: Resultsmentioning
confidence: 99%
“…Worth to be notice that DoI, describes the calculation methodology for FCI in its institutional documents, though for the actual computation, it refers to the use of Figure 7. Classification of references by type of FCI described and provenance (Rush, 1991;Kaiser, 1993;Fagan & Kirkwood, 1997;AAPPA, 2000;Vanier, 2000;Ho, E. H. W. Chan, Wong, & M. Chan, 2000;Teicholz & Edgar, 2001;Brooks, 2004;Uzarski & Grussing, 2008;IFMA, 2008;Roberts, 2009;Lavy et al, 2010Lavy et al, , 2014bBello & Loftness, 2010;Attalla, MacDonald, & Dunn, 2012;Lavy, 2013;Karanja & Mayo, 2016;Dejaco et al, 2017) Complex Differs from the previous for the calculation methodology of deferred maintenance and current replacement value (Capital Asset Management -Asset Strategies, 2011;Geldermann & Sapp, 2007;Kaiser, 2009;Maltese et al, 2017;Quirk, 2006;Rashedi & Hegazy, 2016;Selman & Schneider, 2004) Combined Indicators derived from the basic or extended version of FCI, combined with other metrics (Federal Facilities Council, 2001;Mills, 2001;NASA, 2003;Selman, 2003 Since the definition of its first version in Eq. (1), the indicator had been revised and other versions have been proposed.…”
Section: Fci Calculation Methodsmentioning
confidence: 99%
“…Even if it has been demonstrated that economic and financial indicators are too narrow to achieve a comprehensive knowledge of assets' performances (Pärn, Edwards, & Sing, 2017;Yang et al, 2010), they are widely used in Asset Management (AM). Thus, the aim of this research is to present a critical review concerning the Facility Condition Index (FCI): one of the most acknowledged financial indicators (Lavy, Garcia, & Dixit, 2010, 2014a, 2014b. The FCI allows to quantify in a scale from 0 to 100 (where 0 represents the best value) the condition of an asset, based on the expense dedicated to maintenance operations, calculated as the ratio between the cost of Deferred Maintenance (DM) over the Current Replacement Value (CRV).…”
Section: Introductionmentioning
confidence: 99%
“…Suitability of a space for specific activities is commonly identified as a functionality indicator (Lavy et al, 2014). Thermal comfort, humidity control, air quality, light quality, noise and workplace pollution are generally considered as indicators of comfort/well-being that are also related to functional performance (Atzeri et al, 2016, Ornetzeder et al, 2016.…”
Section: Operational Indicatorsmentioning
confidence: 99%